Elaine Steinbeck at Grapes of Wrath 50th Anniversary Party - unknown:::Creator::::::::::::
Elaine Steinbeck (center) poses with unidentified man and woman at The Grapes of Wrath 50th Anniversary. The photo is very similar to number 1-014.